Cross-domain service chain mapping mechanism based on Q-learning - Hongqi ZHANG; Rui HUANG; Yingjie YANG; Dexian CHANG; Liancheng ZHANG (Tongxin xuebao)
A virtual service resources controlling architecture with regional centralized management and global coordinated scheduling was proposed for the problem of cross-domain service chain mapping in SDNFV environment. On this basis, an effective mapping framework was built and the cross-domain mapping problem was modeled as an ILP with the purpose of minimizing mapping cost. A partitioning algorithm was designed to solve the problem based on Q-learning mechanism under this framework. Simulation results show that the performances of this method are better than other traditional methods on average partition time, average mapping cost, and acceptance ratioof service chain mapping request.